(untitled) (Phenomenology, Humanities and Sciences, 2025)
This article deals with the conscious and unconscious dimensions of mental life. I distinguish the transitive sense of consciousness, being conscious of something, intentionality, from the adjectival or adverbial sense, being conscious or consciously directed towards something. I show that an intentional act can be conscious or unconscious in the second sense and argue that, from this position, we can ask good questions about what consciousness is and its function in mental life. To achieve this result, I begin by framing the topic in the tradition of psychology before Husserl, namely Lipps, and Brentano, and then describe the unconscious dimension from the conceptual apparatus of phenomenology